Role of T cell metabolism in brain tumor development: a genetic and metabolic approach - Bo Yang; Zhenyu Li; Peiliang Li; Bo Liang; Yuhan Liu; Enshan Feng (BMC Neurology)
Abstract Background Malignant brain tumors are among the most lethal cancers. Recent studies emphasized the crucial involvement of the immune system, especially T cells, in driving tumor progression and influencing patient outcomes. The emerging field of immunometabolism has shown that metabolic pathways play a pivotal role in regulating immune responses within the tumor microenvironment. This study aims to clarify the relationships between specific T cell phenotypes, circulating metabolites, and malignant brain tumors. Methods We utilized a multiple mendelian randomization approach to investigate the associations between T cell phenotypes and malignant brain tumors, as well as the role of plasma metabolites in mediating these interactions. Instrumental variables were selected based on stringent criteria, and multiple mendelian randomization methods were utilized to identify causal pathways and metabolites potentially mediating these effects. Results Our analysis identified significant associations between seven distinct T cell phenotypes, including various CD8 + and regulatory T cell subsets, and the presence of malignant brain tumors. We also identified 87 plasma metabolites correlated with these tumors. Notably, metabolites such as octadecanedioylcarnitine (C18-DC) and eicosanedioate (C20-DC) were implicated in modulating the risk of developing malignant brain tumors. Furthermore, metabolites such as 5-dodecenoate (12:1n7) and arachidonate (20:4n6) were found to influence tumor risk, particularly in relation to CD28 − CD8 + T cells. Conclusion The study identifies key T cell phenotypes and plasma metabolites involved in the pathogenesis of malignant brain tumors, offering potential biomarkers and therapeutic targets for future interventions.